IXME: Informatics by Maker Education: A Teacher Training Course on Maker Education in Informatics (Constructionism Conference Proceedings, 2025)
Starting in the school year 2023/2024, informatics became a compulsory subject in grade 10 in Lower Saxony, a federal state in Germany. The core curriculum advises a project and product oriented work, following a constructivistic approach as offered by making acitivities. Since maker education implies a different form of teaching in schools, the question arises how teachers can be supported in integrating maker education into their informatics lessons and which changes can occur as a result of this support. Therefore, the teacher training course “IXME” (abbr. for “Informatics by Maker Education”) was developed und conducted. Qualitative and quantitative data were collected, and are under ongoing analysis following a mixed methods research design.